A Critical Appraisal of Advances in Pediatric Nonalcoholic Fatty Liver Disease - Ovchinsky, Nadia; Lavine, Joel E. (Seminars in Liver Disease, 2012)
Nonalcoholic fatty liver disease (NAFLD) is the most common cause of liver disease in children; its rise has been related to the increasing prevalence of obesity. Significant advancements have been made in the investigation of the etiopathogenesis and genetic risk factors for the disease. Pediatric fatty liver disease often displays a histologic pattern distinct from that found in adults, and liver biopsy remains the gold standard for diagnosis of nonalcoholic steatohepatitis (NASH). Lifestyle modifications that result in weight loss remain the first-line treatment of NAFLD in children. Recent adult and pediatric clinical trials on the use of antioxidants combined with lifestyle intervention for NAFLD have demonstrated encouraging results, and additional trials are underway. In this review, the authors provide an overview of current concepts in epidemiology, histologic features, diagnosis, pathophysiology, genetic risk factors, and treatment of NAFLD in children.
Keywords: nonalcoholic fatty liver disease (NAFLD); nonalcoholic steatohepatitis (NASH); pediatrics; obesity